2010
DOI: 10.1103/physrevlett.104.137202
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Wave-Assisted Thermal Reversal of Epitaxial Perpendicular Magnetic Nanodots

Abstract: The magnetic susceptibility of self-organized two-dimensional Co nanodots on Au(111) has been measured as a function of their size in the 2-7 nm diameter range. We show that the activation energy for the thermal reversal displays a power law behavior with the dot volume. Atomic scale simulations based on the Heisenberg Hamiltonian show that this behavior is due to a deviation from the macrospin model for dot size as small as 3 nm in diameter. This discrepancy is attributed to finite temperature effects through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
(28 reference statements)
0
30
1
Order By: Relevance
“…Two size and anisotropy distributions have been considered; see Figs The perpendicular magnetic anisotropy energy of 1 AL high clusters is considerably larger than the ones reported for 2-AL-high Co islands with comparable size grown on Au(111) and Au(788). The reported values include the shape anisotropy and are K = 0.25-0.42 meV/atom [32], 0.3 meV/atom [33] on Au(111), and K = 0.22 ± 0.19 meV/atom [29], 0.37 ± 0.04 meV/atom [5] on Au(788). Therefore the MAE of 1-AL islands on GdAu 2 /Au(111) is significantly larger than the one of 2-AL Co islands grown on Au(111) and Au(788).…”
Section: B Below the Coalescence Thresholdmentioning
confidence: 99%
“…Two size and anisotropy distributions have been considered; see Figs The perpendicular magnetic anisotropy energy of 1 AL high clusters is considerably larger than the ones reported for 2-AL-high Co islands with comparable size grown on Au(111) and Au(788). The reported values include the shape anisotropy and are K = 0.25-0.42 meV/atom [32], 0.3 meV/atom [33] on Au(111), and K = 0.22 ± 0.19 meV/atom [29], 0.37 ± 0.04 meV/atom [5] on Au(788). Therefore the MAE of 1-AL islands on GdAu 2 /Au(111) is significantly larger than the one of 2-AL Co islands grown on Au(111) and Au(788).…”
Section: B Below the Coalescence Thresholdmentioning
confidence: 99%
“…Spin-wave excitation has already been shown to play a significant role in magnetic reversal in several theoretical works using classical approaches. 9,15,16 Finally, one can also examine the effect of injecting electrons with a nonpolarized spin. In that case, for asymptotically long times, the system is not entirely in the ground state.…”
Section: Magnetization Switch Induced By Injected Electronsmentioning
confidence: 99%
“…The development of spin-polarized scanning tunneling microscopy (SP-STM) led to detailed observations of the thermally induced magnetic switch in small ferromagnets, allowing a detailed test of the global rotation of the Néel-Brown view and of its limits. [3][4][5][6][7][8][9][10] In parallel, analyses led to the discussion of other views of the thermally activated magnetization switch, [10][11][12][13][14][15][16][17] for example, spin-wave contributions, nucleation, edge effects, and anisotropy effect. Following earlier works on multilayered materials, 18,19 SP-STM experiments revealed that injection of spin-polarized electrons into a nanoferromagnet could also switch its magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…In all of these applications a crucial role is played by spin waves. They also have a significant influence on the stability of the magnetic configuration [29,30], even if the system is smaller than the characteristic exchange length [31]. Because of their importance spin wave excitations in magnetic dots have been widely studied in numerous papers experimentally [32][33][34][35][36][37], theoretically [38][39][40][41][42][43], and by means of numerical simulations [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%